RANTAI PASOK KOMODITAS KACANG TANAH DI KABUPATEN MUNA - Abdul Rahman; Usman Rianse; Sitti Aida Adha Taridala (Jurnal Sosio Agribisnis, 2019)
This research aims to analyze (1) supply chain path, and (2) the performance of a supply chain commodity peanut Muna Regency. Sampling method used in this research was simple random sampling and snowball sampling. Supply chain path analyzed in qualitative descriptive. Supply chain performance is analyzed with a model approach to Supply Chain Operations Reference (SCOR). The results showed that members of the supply chain consists of peanut farmers, village collector (PPD), Sub-district collector (PPK) and inter-insular traders (PAP). There are three pathways of a supply chain that is a path I: farmer → PPD → PAP; path II: farmer → PPK → PAP; and path III: farmer → PAP. Supply chain performance attributes based on shipping and order fulfillment cycle, farmers are in the position and traders are at a good position..Keywords: peanuts; supply chains; traders; SCOR